Detection of coconut cadang-cadang viroid variants (CCCVd) in coconut by reverse transcription loop-mediated isothermal amplification (RT-LAMP) - Mat Husain, Siti Rohani (2015)
Coconut cadang-cadang disease is a major destructive disease in coconut palms in the Philippines caused by Coconut cadang-cadang viroid (CCCVd). CCCVd variants have been characterized in Malaysia’s oil palms associated with orange spotting disease. Recently, CCCVd variant was also reported in Malaysian coconut. Detection and characterization of the variants was reported to be difficult due low concentration in infected hosts. Molecular techniques like polyacrylamide gel electrophoresis (PAGE), hybridization assay and conventional RT-PCR have been widely used for detection of CCCVd in coconut but they were not reliable due to their low concentrations. RT-LAMP is a novel method which depends on auto-cycling strand displacement DNA synthesis performed by a Bst DNA polymerase and under isothermal conditions (60-65ºC). The assay is high specificity with use of four target specific primers which recognizes six distinct regions of the sequence. This study was conducted to detect CCCVd variants in coconut using the RT-LAMP and validated by RT-PCR using CCCVd specific and LAMP primers. Total nucleic acid was extracted using N-STEP extraction from nine coconut samples that showed CCCVd infection-like symptoms. The nucleic acid was amplified by RT-LAMP with CCCVd specific primers. The amplicons analysed by 2% agarose gel electrophoresis. The results of this study show that CCCVd variants were detected in coconut samples using RT-LAMP assay. Two (AL2 and AL3) out of nine coconut samples were positive for the presence of CCCVd by RT-LAMP assay. The optimized condition for RT-LAMP assay for coconut samples were at 65ºC for 60 min. The N-STEP extraction procedure used in this study may not be suitable for RT-PCR analysis as no amplification was observed in RT-PCR using CCCVd specific and LAMP primers.